An in-silico approach to design a vaccine against beta lactamase enzyme of mycobacterium tuberculosis - Meem, Fatiha Soumaiya (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2022.